Workshop Pelatihan Learning Management System (LMS) Untuk Peningkatan Kualitas Pembelajaran Jarak Jauh Di SMP Negeri 242 Jakarta - Achmad Nur Hidayaht; Nandi Kurniawan; Nurul Istiqomah (Bahasa Indonesia, 2022)
This community service activity is to provide training in designing online learning through the use of the Edmodo online platform for teachers of SMP Negeri 242 Jakarta. This is due to the Covid-19 pandemic which requires learning activities to be carried out from home (PJJ). The ability of teachers to utilize digital learning platforms by moving offline learning to online learning, as well as organizing student assignments into competencies that must be mastered and improved in order to create synchronous and asynchronous learning. The application of Edmodo is a learning alternative that creates effective learning to support the process of organizing learning activities because Edmodo has several features, such as "Assignment", "Quiz", and "Poll" and several other features such as cloud for material storage. This training activity was attended by 26 teachers of SMP Negeri 242 Jakarta from various subject teachers. The training is carried out online and offline. The data acquisition instrument used a questionnaire which was used to determine the initial perceptions and insights of the training participants towards the BDR learning that had been carried out and to find out their perceptions and insights after attending the training. Based on the results of the questionnaire, the training that has been carried out has had a positive and beneficial impact on the teachers of SMP Negeri 242 Jakarta.